Histórias e relatos sobre Pipa: a praia internacional do Rio Grande do Norte - Aires, Jussara Danielle Martins (2012)
The overwhelming gear that boosted tourism as the main economic activity of Pipa a district formerly agricultural and fishery, that belongs to the municipality of Tibau do Sul/RN produced significant changes in the social, economic and cultural rights of the native population of the place where social relations were narrow and justified in some cases, the line of kinship in an environment where all residents knew each other. However, we can not observe the emergence of this activity just as voracious disarticulator of old local forms of sociability that in a linear process, destroys the old, replacing it with the new. New compositions are generated by merging elements of past and present. Overcoming opposition to simplistic positive or negative impacts of tourism sought especially in this dissertation, review the history of Pipa (told in narrative form), showing how slowly this district has become a major international tourist destination and how its residents were being swallowed by the "whirlwind" that led to this reality. The research used qualitative methodology and was based on photographic, literature and survey, observation, experience, oral and written reports acquired in the field. We conducted in-depth interviews (oral history) with subjects that are the living memory of the place local residents (mostly natives). We found that before the process of "modernization" resulting from the pressure of globalization itself and the capital investment in tourism resulting from the native population is not passive. On the contrary, natives resist, creating mechanisms of material and symbolic reformulations. The present moment is always dynamic. Because of that, the identity of a place is not the crystallization of its past. Many landscapes still reveal materialities of yesteryear, such as registration of social practices in the construction of the place